(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Cellular manufacturing system is the nerve of industry in our days and many studiesand researches discussed in this field . In this research row materials need to cross longdistance about thousand meters during the manufacturing process to be final product inALWAZIRIA ELECRICAL MOTOR FACTORY the problem was needed to reduce therouting of row material flow and increase flexibility with saving same operation sequence .First segmented the facility into subsystems called cells and figured the system output .theresearch goes in two ways first assign the problem and parameter affected on productionprocess secondly apply the particle swarm to the problem after writing the algorithms. Theparticle swarm technique shows great flexibility in scheduling purposes problem. Also theproduct will cross about 400 m instead of 1000 m before using PSO after extracted theresult which it discussed and recommended to the future researcher .